Association between a combination of cognitively stimulating leisure activities and long-chain polyunsaturated fatty acid intake on cognitive decline among community-dwelling older Japanese individuals - Tokuda, Hisanori; Horikawa, Chika; Nishita, Yukiko; Kaneda, Yoshihisa; Obata, Hidenori; Rogi, Tomohiro; Izumo, Takayuki; Nakai, Masaaki; Shimokata, Hiroshi; Otsuka, Rei (Frontiers in Aging Neuroscience, 2024)
Multifactorial lifestyle approaches could be more effective than a single factor for maintaining cognitive function. This study investigated the association of combining cognitively stimulating leisure activities (CSLAs), including puzzles, quizzes, and cognitive training games, with intake of long-chain polyunsaturated fatty acids (LCPUFAs), including docosahexaenoic acid (DHA), eicosapentaenoic acid (EPA), and arachidonic acid (ARA), on cognitive function in the older Japanese individuals without dementia. Participants were community-dwelling Japanese individuals without a self-reported history of dementia (n = 906, aged 60–88 years) from datasets of a 2-year longitudinal study (baseline: 2006–2008 and follow-up: 2008–2010). CSLA engagement and LCPUFA intake were divided into high and low groups according to frequency (≥once/week and <once/week) for CSLA engagement and median intake level for LCPUFA intake according to sex, then categorized into four groups. The associations of multivariate-adjusted odds ratio (OR) for a cognitive decline, shown as a decrease in the Mini-Mental State Examination score by 2 or more points, and the combination of CSLA engagement with LCPUFA intake were assessed using a multiple logistic regression model. Subgroup analysis involved participants with low DHA and EPA intakes (n = 303; median intake, 325 mg/day), mirroring those in North America. The HIGH-CSLA/HIGH-ARA group cumulatively yielded a lower OR for cognitive decline (0.41; 95% confidence interval, 0.25–0.70) than did the LOW-CSLA/LOW-ARA group (p for trend = 0.001). In the subgroup analysis, the OR for the HIGH-CSLA/HIGH-DHA group was notably reduced (0.31; 95% confidence interval, 0.11–0.87; p for trend = 0.025) compared with the LOW-CSLA/LOW-DHA group. High CSLA engagement frequency combined with high ARA intake may cumulatively reduce the risk of cognitive decline among older Japanese individuals. Furthermore, combining CSLA engagement frequency with DHA intake could have a positive association with maintaining cognitive function among older individuals, particularly those with low DHA and EPA intakes.